A Treatable Neurometabolic Disorder: Glutaric Aciduria Type 1. (27th January 2014) - Pusti, S.; Das, N.; Nayek, K.; Biswas, S.
Abstract : Glutaric aciduria type 1 (GA-1) is an autosomal recessive disorder of lysine, hydroxylysine, and tryptophan metabolism caused by deficiency of glutaryl-CoA dehydrogenase. It results in the accumulation of 3-hydroxyglutaric and glutaric acid. Affected patients can present with brain atrophy and macrocephaly and with acute dystonia secondary to striatal degeneration in most cases triggered by an intercurrent childhood infection with fever between 6 and 18 months of age. We report two such cases with macrocephaly, typical MRI pictures, and tandem mass spectrometry suggestive of glutaric aciduria type 1.